Comparative Analysis of the Ecological-Floristic Classification and the Russian Forest Typologies - Natalya S. Ivanova; Valery V. Fomin; Sergey V. Zalesov; Anna P. Mikhailovich (Лесной журнал, 2024)
At the beginning of the 20th century in Europe, a scientific direction was formed, called phytosociology, the founder of which was the Swiss botanist and ecologist J. Braun- Blanquet. The approach he developed has become widespread throughout the world and has formed the basis for a large number of vegetation classifications. The article provides a description of the ecological-floristic approach to vegetation classification according to the following parameters: the scope of the concept of association, the peculiarities of its boundary allocation, the classification criteria for establishing the type of forest conditions and for determining the association, consideration of the succession dynamics and the influence of anthropogenic factors, the level of implementation in forestry, forest management and reporting. An overview of the current state of the approach is given and the results of its comparison to the Russian forest typologies are presented. The advantages of the Braun-Blanquet classification include its versatility, developed methodology, flexibility of classification criteria and a carefully thought-out nomenclature. The development of the Turboveg software package for entering, storing and processing vegetation data has contributed to the increase in the use of this classification. Currently, in addition to vegetation features, it is becoming mandatory to take into account climatic parameters, and when identifying syntaxa and forming cartographic representations of vegetation, modern advances in the field of GIS technologies are used to assess the factors that influence the vegetation structure. The reflection of successional dynamics in syntaxonomic units still remains an urgent task for both the ecological-floristic approach and the domestic forest typologies. Within the framework of the Braun-Blanquet approach, aspects related to the consideration of anthropogenic transformations of plant associations are also being actively studied. This is evidenced by a number of successful examples of assessing forest synanthropization and modeling the response functions of plant communities to environmental factors, including anthropogenic ones. As in forest typologies, multidimensional methods of data analysis (DCA, CCA, PCA with superimposition of vectors on ordination diagrams) are widely used in the development of eclological-floristic classifications for studying the structure of forest vegetation.